Mentoring in Initial Teacher Education: Practices and Needs for Continuing Professional Development of Romanian School-Based Teacher Educators - Mirela Scorţescu; Simona Lidia Sava; Mariana Craşovan (SAGE Open)
Practical training is an important component of initial teacher education (ITE). Interactions with the educational reality in schools and with school-based teacher educators (SBTEs) are crucial to practical training. Often, SBTEs lack specific and consistent training to work with future teachers. This study aimed to identify the practices and needs of SBTEs guiding the pedagogical practicum of students, future teachers working in Romanian kindergarten and primary education. A questionnaire provided by the International Forum for Teacher Educator Development (InFo-TED) was administered in December 2021 to January 2022 to 116 SBTEs conducting mentoring activities for future teachers in primary schools and kindergartens. The analysis of their responses by level of education and experience highlighted the perceived usefulness of activity types considered relevant and less relevant in mentoring, training activities previously accessed, professional training needs, and how research is valued in mentoring. Specific training practices and needs are highlighted, providing grounds for developing training programs and interventions aimed at enhancing SBTEs’ competencies in mentoring prospective teachers.